2017
DOI: 10.1186/s12893-017-0280-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of perigastric tumor deposits in patients with primary gastric cancer

Abstract: BackgroundThe presence and the prognostic significance of perigastric tumor deposits (TDs) in primary gastric cancer have not been extensively studied. The aim of this study was to evaluate the prognostic significance perigastric TDs in primary gastric cancer.MethodsFrom 2005 to 2010, 1250 patients underwent R0 gastrectomy at the Department of Gastric Surgery, Fujian Medical University Union Hospital, Fuzhou, China. Out of 1250 patients, 132 patients with perigastric TDs were identified. Additionally, 132 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 18 publications
2
29
1
Order By: Relevance
“…Eight studies were included in the meta‐analysis to correlate TD presence with patient overall survival and with other prognostic factors such as lymph node metastasis (LNM) and invasion depth. For lymph vessel invasion (LVI) only five could be included, and only four for vascular invasion (VI) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight studies were included in the meta‐analysis to correlate TD presence with patient overall survival and with other prognostic factors such as lymph node metastasis (LNM) and invasion depth. For lymph vessel invasion (LVI) only five could be included, and only four for vascular invasion (VI) .…”
Section: Resultsmentioning
confidence: 99%
“…With the information from the studies we included and the correlation we observe with poor prognostic factors, we are inclined to believe that the second hypothesis might be the most factual hypothesis. Some of the studies included even provided a TNM adjustment for their cases, and found that patients with TDs had similar survival curves to those patients without TDs but with N3, M1 or T4 staging . Another study proposed they should be included in the N‐category not because of their origin, but because in their cohort, TD+ patient survival behaved more like that of pN1 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 8th edition of AJCC gastric cancer staging manual 19 , TDs without identi able lymph node tissue or identi able vascular or neural structure, regardless of their shape, contour and size, are considered as regional LN metastases for the purposes of gastric cancer staging. However, some research suggested that TDs in GC should be incorporated into the T category and treated as a form of serosal invasion 20,21 . Nevertheless, the prognostic impact of TDs is undeniable, the algorithm of staging with TDs is controversial.…”
Section: Discussionmentioning
confidence: 99%